Makna Qiradah dalam Kisah Bani Israil - Aidah Mega Kumalasari (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2021)
This paper discusses the meaning of qiradah contained in QS. Al-Baqarah [2]:65. The meaning of qiradah has been interpreted by the community as monkeys. Even though the word qiradah is not only interpreted in an essential way. This study aims to find various meanings of qiradah with several verses using a semiotic approach. In this study, the author uses Roland Barthes' semiotic approach, namely denotation and connotation to reveal the meaning of qiradah. To achieve this goal, this research uses qualitative methods. The results of this study conclude that: First, in the linguistic system or the denotative meaning of the word qiradah, it does not only mean monkeys, but monkeys that have no shame. Second, the system of mythology or connotative meaning. The word qiradah in this system shows not the physical meaning, but the disgraceful nature that positions a person in humiliation. the interpretation of the verses of the Qur'an related to animals needs to be developed in order to expand the study of the science of interpretation of the Qur'an in order to prove the dynamic elements of the Qur'an.